Protestant enlightenment(s)? The origins and dissemination of enlightenment theology in Anglicanism, German Lutheranism, and Swedish Lutheranism - Laitenberger, H (2021)
Since the early 2000s, intellectual historians have increasingly emphasised that Enlightenment and revealed religion could be reconciled, contradicting traditional depictions. A growing body of scholarship on the so-called ‘religious Enlightenment’ – spanning Catholicism, Judaism, and Protestantism – has developed as a result of this shift. However, the attempts to subsume the enlightened representatives of all faiths into one supra-confessional Enlightenment has gradually confused the understanding of ‘enlightened religion’, especially in the Protestant context. To counter this development, this thesis seeks to re-establish the existence of a particular and uniform Protestant Enlightenment that spanned Anglicanism, German Lutheranism, and Swedish Lutheranism during the ‘Long Eighteenth Century’. To this end, it presents an intellectual and cultural history of enlightened theology within these Churches, based on the existing historiography and its foundational texts and figures: first, it offers a comparative analysis of the theologies of Ralph Cudworth, Henry More, Gottfried Wilhelm Leibniz, Joseph Butler, and Johann Joachim Spalding. It thereupon examines the reception of their theologies in Swedish Lutheranism through the correspondences of Eric Benzelius the Younger and Jacob Axelsson Lindblom’s periodical Journal för Prester. Based on this, the thesis argues that – certain differences notwithstanding – there was a recognisable single Protestant Enlightenment whose quintessential hallmark was an intellectualist natural theology that emphasised the fundamental benevolence of God and the harmony of the universe, as well as the fundamental freedom and reasonableness of humanity. Mostly emerging as a result of ‘crises of orthodoxy’ that made stringent confessional uniformity untenable, this creed built on Platonic-Erasmian foundations and the seventeenth century’s scientifico-philosophical advances. While rejecting much of the Reformation’s Augustinian ideas, it was nonetheless distinctly Protestant in character by professing an individualistic, emancipatory faith that appealed to Anglicans and Lutherans alike. Indeed, by the eighteenth century’s close, it had in parts morphed into a self-conscious movement.